Adhesive sheet, optical film with adhesive sheet, and method for producing adhesive sheet and optical film with adhesive sheet
By using a photocurable adhesive composition and antioxidant, combined with the reuse technology of release liner, the problems of environmental burden and energy consumption in the adhesive sheet manufacturing process are solved, and a low environmental burden and efficient adhesive sheet manufacturing are achieved.
Patent Information
- Application Number
- CN202380055644.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-22
- Filing Date
- 2023-07-21
- Publication Date
- 2025-03-14
AI Technical Summary
During the manufacturing process of existing adhesive sheets, a large amount of release liner is required, resulting in a large environmental burden and a high energy consumption of the adhesive sheet.
A photocurable adhesive composition is employed, including (meth)acrylic monomer, partial polymer and photopolymerization initiator, and an antioxidant is added to the adhesive composition to inhibit the increase in the release force of the release liner. The adhesive is cured by irradiation with light, and the adhesive sheet having a thickness of 5 to 100 μm is formed, and the release liner is reused to reduce the amount of waste.
The amount of waste of release liner during the adhesive sheet manufacturing process is reduced, the environmental burden is reduced, and the manufacturing efficiency of the adhesive sheet is improved.
Smart Images

Figure CN119630751A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a pressure-sensitive adhesive sheet, an optical film with a pressure-sensitive adhesive sheet, and methods for producing the pressure-sensitive adhesive sheet and the optical film with a pressure-sensitive adhesive sheet. Background Art
[0002] Various image display devices represented by liquid crystal display devices and electroluminescent (EL) display devices generally have an optical laminate including an optical film such as a polarizing film and an adhesive sheet. Adhesive sheets are usually used to bond the optical films contained in the optical laminate and to bond the optical laminate to the image display panel. As an adhesive sheet, a typical sheet is obtained by curing a monomer group including an acrylic monomer, a silicone monomer, etc. by polymerization and crosslinking.
[0003] An example of a PSA sheet is disclosed in Patent Document 1. In Patent Document 1, the PSA sheet is produced by irradiating a coating layer of a PSA composition disposed between two release liners with light.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent No. 6688054 Summary of the invention
[0007] Problems to be solved by the invention
[0008] When forming an adhesive sheet by curing, heat, light and other energies are usually required. According to the method using light (photocuring method), compared with the method (thermal curing method) in which, for example, a coating layer comprising an adhesive composition and a solvent is thermally cured by an oven, the energy required for the formation of the adhesive sheet can be reduced. However, from the viewpoint of reducing the environmental burden during the manufacture of the adhesive sheet, it is insufficient to focus only on the energy required for the curing of the coating layer.
[0009] Therefore, an object of the present invention is to provide a PSA sheet that can be produced with a low environmental burden by reducing the amount of waste of release liners required for producing the PSA sheet.
[0010] Solutions to the problem
[0011] The present invention provides an adhesive sheet, which is formed by a photocurable adhesive composition, wherein the photocurable adhesive composition comprises a monomer group containing a (meth)acrylic monomer and / or a partial polymer of the monomer group, and a photopolymerization initiator.
[0012] The thickness of the adhesive sheet is 5 to 100 μm.
[0013] The adhesive composition further comprises an antioxidant,
[0014] The antioxidant comprises at least one selected from hindered phenol compounds, hindered amine compounds and phosphorus compounds, and has a molecular weight of less than 1000.
[0015] In addition, the present invention provides an optical film with a pressure-sensitive adhesive sheet, comprising:
[0016] The above adhesive sheet, and
[0017] Optical film.
[0018] In addition, the present invention provides a method for producing a pressure-sensitive adhesive sheet, which is the method for producing the pressure-sensitive adhesive sheet described above.
[0019] The manufacturing method comprises:
[0020] A step of irradiating light on a laminate comprising a substrate sheet, a coating layer containing the adhesive composition, and a release liner in this order to form the adhesive sheet having a thickness of 5 to 100 μm from the coating layer; and
[0021] step B of peeling the release liner from the adhesive sheet,
[0022] The above-mentioned step A and the above-mentioned step B are repeatedly carried out using the above-mentioned release liner released in the above-mentioned step B, and the above-mentioned release liner is reused.
[0023] In addition, the present invention provides a method for manufacturing an optical film with an adhesive sheet, the method comprising:
[0024] The pressure-sensitive adhesive sheet formed by the above-mentioned production method is laminated on an optical film to form an optical film with a pressure-sensitive adhesive sheet.
[0025] Effects of the Invention
[0026] According to the present invention, it is possible to provide a PSA sheet that can be produced with a low environmental burden by reducing the amount of waste of release liners required for producing the PSA sheet. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a cross-sectional view schematically showing an example of the pressure-sensitive adhesive sheet of the present invention.
[0028] Figure 2A This is a schematic diagram for explaining a method for measuring the creep amount of a PSA sheet.
[0029] Figure 2B This is a schematic diagram for explaining a method for measuring the creep amount of a PSA sheet.
[0030] Figure 3 This is a schematic diagram for explaining an example of the method for producing the pressure-sensitive adhesive sheet of the present invention.
[0031] Figure 4 This is a cross-sectional view schematically showing an example of a release liner that can be used in the method for producing the pressure-sensitive adhesive sheet of the present invention.
[0032] Figure 5 This is a schematic diagram for explaining an example of the method for producing the pressure-sensitive adhesive sheet of the present invention.
[0033] Figure 6 This is a schematic diagram for explaining an example of the method for producing the pressure-sensitive adhesive sheet of the present invention.
[0034] Figure 7 This is a cross-sectional view schematically showing an example of the optical film with a pressure-sensitive adhesive sheet of the present invention.
[0035] Figure 8 This is a cross-sectional view schematically showing an example of the optical film with a pressure-sensitive adhesive sheet of the present invention. DETAILED DESCRIPTION
[0036] The first aspect of the adhesive sheet of the present invention is formed of a photocurable adhesive composition containing a monomer group containing a (meth)acrylic monomer and / or a partial polymer of the monomer group and a photopolymerization initiator.
[0037] The thickness of the adhesive sheet is 5 to 100 μm.
[0038] The adhesive composition further comprises an antioxidant,
[0039] The antioxidant comprises at least one selected from hindered phenol compounds, hindered amine compounds and phosphorus compounds, and has a molecular weight of less than 1000.
[0040] In a second aspect of the present invention, for example, in the pressure-sensitive adhesive sheet of the first aspect, the antioxidant includes a hindered phenol compound.
[0041] In a third aspect of the present invention, for example, in the pressure-sensitive adhesive sheet of the first or second aspect, the molecular weight of the antioxidant is 500 or less.
[0042] In a fourth aspect of the present invention, for example, in the PSA sheet according to any one of the first to third aspects, the amount of the hydroxyl group-containing monomer blended is less than 5 parts by weight in 100 parts by weight of the monomer group.
[0043] In a fifth aspect of the present invention, for example, in the PSA sheet according to any one of the first to fourth aspects, the monomer group includes a carboxyl group-containing monomer.
[0044] In a sixth aspect of the present invention, for example, in the PSA sheet according to any one of the first to fifth aspects, the content of the solvent in the PSA composition is 5% by weight or less.
[0045] The optical film with a pressure-sensitive adhesive sheet according to a seventh aspect of the present invention comprises:
[0046] The pressure-sensitive adhesive sheet according to any one of the first to sixth aspects, and
[0047] Optical film.
[0048] In an eighth aspect of the present invention, for example, in the optical film with a pressure-sensitive adhesive sheet of the seventh aspect,
[0049] The optical film is a film including at least one selected from a polarizing film and a retardation film.
[0050] A method for producing a PSA sheet according to a ninth aspect of the present invention is the method for producing a PSA sheet according to any one of the first to sixth aspects,
[0051] The manufacturing method comprises:
[0052] A step of irradiating light on a laminate comprising a substrate sheet, a coating layer containing the adhesive composition, and a release liner in this order to form the adhesive sheet having a thickness of 5 to 100 μm from the coating layer; and
[0053] step B of peeling the release liner from the adhesive sheet,
[0054] The above-mentioned step A and the above-mentioned step B are repeatedly carried out using the above-mentioned release liner released in the above-mentioned step B, and the above-mentioned release liner is reused.
[0055] The method for producing an optical film with a pressure-sensitive adhesive sheet according to a tenth aspect of the present invention includes:
[0056] The pressure-sensitive adhesive sheet formed by the production method of the ninth aspect is laminated on an optical film to form an optical film with a pressure-sensitive adhesive sheet.
[0057] Hereinafter, the present invention will be described in detail, but the present invention is not limited to the following embodiments and can be implemented with arbitrary modifications within the scope not departing from the gist of the present invention.
[0058] The present inventors have come up with the idea of further reducing the environmental burden in the production process of a PSA sheet by reusing a release liner that would otherwise be discarded immediately after release, and have conducted studies based on this idea, leading to the completion of the present invention.
[0059] [Embodiments of Adhesive Sheet]
[0060] An example of the pressure-sensitive adhesive sheet of this embodiment is shown in Figure 1 . Figure 1The adhesive sheet 1 is formed by an adhesive composition. The adhesive composition comprises a monomer group containing a (meth) acrylic monomer and / or a partial polymer of the monomer group, and a photopolymerization initiator. The adhesive composition is a photocurable adhesive composition that is cured by irradiation with light. In this specification, a photocurable adhesive composition is sometimes referred to as a photocurable composition.
[0061] The adhesive composition further includes an antioxidant D. The antioxidant D contained in the adhesive composition includes at least one selected from hindered phenol compounds, hindered amine compounds and phosphorus compounds, and has a molecular weight of 1000 or less. According to the adhesive composition including the antioxidant D, there is a tendency to suppress the increase in the peeling force of the release liner relative to the adhesive sheet 1 when manufacturing the adhesive sheet 1. Therefore, the release liner can be reused. As a result, the amount of waste of the release liner can be reduced, and the adhesive sheet 1 can be repeatedly manufactured under low environmental burden.
[0062] The thickness of the adhesive sheet 1 is 5 to 100 μm, preferably 5 to 50 μm, more preferably 5 to 25 μm, and further preferably 5 to 20 μm. Since the thickness of the adhesive sheet 1 is less than 100 μm, there is a tendency that the absolute amount of residual monomers is less than that of an adhesive sheet having a thickness greater than 100 μm. Therefore, when manufacturing the adhesive sheet 1, the surface of the release liner is not easily contaminated by the residual monomers, and the tendency to increase the release force of the release liner relative to the adhesive sheet 1 can be further suppressed. Since the thickness of the adhesive sheet 1 is less than 100 μm, there is a tendency that the end portion is not easily offset even when the optical film shrinks when laminated with an optical film such as a polarizing film. Therefore, in the case of an optical film with an adhesive sheet using the adhesive sheet 1, even in a high temperature environment such as about 85°C or more, it is not easy to have poor appearance such as light leakage caused by the shrinkage of the optical film.
[0063] The pressure-sensitive adhesive sheet 1 may be laminated with a base sheet or a release liner used in its production.
[0064] (Adhesive composition)
[0065] As described above, the adhesive composition of the present embodiment includes a monomer group containing a (meth) acrylic monomer and / or a partial polymer of the monomer group. The content of the (meth) acrylic component in the adhesive composition, i.e., the (meth) acrylic monomer and its partial polymer, can be 50% by weight or more, 60% by weight or more, 70% by weight or more, and further can be 80% by weight or more. In this case, an acrylic adhesive sheet having a (meth) acrylic polymer and its cross-linked product as the main component can be formed. In this specification, (meth) acrylic acid refers to acrylic acid and methacrylic acid. (Meth) acrylate refers to acrylate and methacrylate.
[0066] Examples of (meth)acrylic monomers include (meth)acrylic acid alkyl esters having an alkyl group having 1 to 20 carbon atoms in a side chain. The number of carbon atoms in the alkyl group may be 7 or less, 6 or less, 5 or less, or 4 or less. The alkyl group may be linear or branched. Examples of the alkyl (meth)acrylates are methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-dodecyl (meth)acrylate (lauryl (meth)acrylate), n-tridecyl (meth)acrylate, n-tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, and octadecyl (meth)acrylate. The alkyl (meth)acrylate may be n-butyl (meth)acrylate.
[0067] The content of the alkyl (meth)acrylate in the monomer group may be, for example, 40% by weight or more, 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 85% by weight or more, 90% by weight or more, or even 95% by weight or more. It should be noted that when calculating the content, the weight of the partial polymer is converted into the weight of each monomer before polymerization.
[0068] The monomer group may include a carboxyl-containing monomer. The carboxyl-containing monomer may be a (meth) acrylic monomer, in other words, the (meth) acrylic monomer may include a carboxyl-containing monomer. Examples of carboxyl-containing monomers are (meth) acrylic acid, (meth) carboxylethyl acrylate, (meth) carboxylpentyl acrylate, itaconic acid, maleic acid, fumaric acid and crotonic acid. The content of the carboxyl-containing monomer in the monomer group may be, for example, less than 10% by weight, less than 9% by weight, less than 8% by weight, less than 7% by weight, less than 6% by weight, less than 5.5% by weight, and further less than 5% by weight. The lower limit of the content may be, for example, more than 0.1% by weight, more than 0.5% by weight, and further more than 1% by weight. The monomer group may also not include a carboxyl-containing monomer.
[0069] The monomer group may include a hydroxyl-containing monomer. The hydroxyl-containing monomer may be a (meth) acrylic acid monomer, in other words, the (meth) acrylic acid monomer may include a hydroxyl-containing monomer. The hydroxyl-containing monomer may contribute to the improvement of the cohesive force of the adhesive sheet. Examples of hydroxyl-containing monomers are 2-hydroxyethyl (meth) acrylate, 2-hydroxypropyl (meth) acrylate, 4-hydroxybutyl (meth) acrylate, 6-hydroxyhexyl (meth) acrylate, 8-hydroxyoctyl (meth) acrylate, 10-hydroxydecyl (meth) acrylate, 12-hydroxylauryl (meth) acrylate, and methyl acrylate (4-hydroxymethylcyclohexyl). The hydroxyl-containing monomer is preferably 2-hydroxyethyl (meth) acrylate and 4-hydroxybutyl (meth) acrylate. The content of the hydroxyl-containing monomer in the monomer group is, for example, less than 10% by weight, and may be less than 5% by weight, less than 4% by weight, less than 3% by weight, less than 2% by weight, less than 1% by weight, less than 0.8% by weight, less than 0.5% by weight, less than 0.3% by weight, less than 0.2% by weight, and further may be less than 0.1% by weight. The lower limit of the content may be, for example, 0.01% by weight or more, 0.03% by weight or more, or further 0.05% by weight or more. The monomer group may not contain a hydroxyl group-containing monomer.
[0070] In 100 parts by weight of the monomer group, the amount of the hydroxyl-containing monomer is preferably less than 5 parts by weight. The amount of the hydroxyl-containing monomer is more preferably 4 parts by weight or less, and can be 3 parts by weight or less, 2 parts by weight or less, and further can be 1 part by weight or less. The lower limit of the amount is, for example, 0.01 parts by weight or more, 0.03 parts by weight or more, and further can be 0.05 parts by weight or more.
[0071] In the adhesive composition, each of the above monomers may be included in the form of a partial polymer. The partial polymer may be any polymer of a homopolymer and a copolymer. The partial polymer may contribute to the stable formation of the coating layer by appropriately increasing the viscosity of the adhesive composition.
[0072] As described above, the adhesive composition further includes a photopolymerization initiator. Examples of the photopolymerization initiator include a photoradical generator that generates radicals by visible light and / or ultraviolet light having a wavelength shorter than 450 nm.
[0073] Examples of photopolymerization initiators include benzoin ethers such as benzoin methyl ether, benzoin isopropyl ether, and benzoin dimethyl ether; substituted benzoin ethers such as anisole methyl ether; substituted acetophenones such as 2,2-diethoxyacetophenone and 2,2-dimethoxy-2-phenylacetophenone; α-hydroxyalkyl phenones such as 1-hydroxycyclohexyl phenyl ketone; substituted α-ol ketones such as 2-methyl-2-hydroxypropiophenone; aromatic sulfonyl chlorides such as 2-naphthalenesulfonyl chloride; photoactive oximes such as 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime; benzophenone, benzoylbenzoic acid, benzoylbenzoic acid, Benzophenone compounds such as methyl benzoate, 4-phenylbenzophenone, hydroxybenzophenone, acryloyl benzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone; thioxanthone compounds such as thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, 2,4-diethylthioxanthone; 2,4,6-trichloro-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methoxyphenyl)-4,6 -bis(trichloromethyl)-s-triazine, 2-(p-tolyl)-4,6-bis(trichloromethyl)-s-triazine, 2-piperonyl-4,6-bis(trichloromethyl)-s-triazine, 2,4-bis(trichloromethyl)-6-phenylvinyl-s-triazine, 2-(naphthalene-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-methoxy-naphthalene-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2,4-trichloromethyl-(piperonyl)-6-triazine, 2,4-trichloromethyl-(4'-methoxyphenylvinyl)-6-triazine, etc. Oxime ester compounds such as 1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyloxime)], O-(acetyl)-N-(1-phenyl-2-oxo-2-(4'-methoxy-naphthyl)ethylidene)hydroxylamine; phosphine compounds such as bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyldiphenylphosphine oxide; quinone compounds such as 9,10-phenanthrenequinone, camphorquinone, and ethylanthraquinone; borate ester compounds; carbazole compounds; imidazole compounds; and titanocene compounds. The adhesive composition may contain one or more photopolymerization initiators.
[0074] The amount of the photopolymerization initiator in the adhesive composition is, for example, 0.02 to 10 parts by weight, or 0.05 to 5 parts by weight, relative to 100 parts by weight of the total of the monomer group and the partially polymerized product thereof.
[0075] As described above, the adhesive composition further comprises an antioxidant D. The antioxidant D comprises at least one selected from hindered phenol compounds, hindered amine compounds and phosphorus compounds. Preferably, the antioxidant D comprises at least one selected from hindered phenol compounds and hindered amine compounds, and particularly preferably comprises a hindered phenol compound. Preferably, the compound contained in the antioxidant D does not contain a sulfur atom. The adhesive composition may comprise one or more antioxidants D.
[0076] The molecular weight of antioxidant D is 1000 or less. The molecular weight of antioxidant D is preferably 800 or less, can be 500 or less, and can be 400 or less. The smaller the molecular weight of antioxidant D, the more there is a tendency to further suppress the increase in the peeling force of the release liner relative to the adhesive sheet 1 when manufacturing the adhesive sheet 1. It should be noted that due to the small molecular weight, antioxidant D is preferably liquid at room temperature (25°C). The lower limit of the molecular weight of antioxidant D is not particularly limited, for example, it is 100 or more, can be 200 or more, and can be 300 or more.
[0077] Examples of hindered phenol compounds include butylated hydroxytoluene (BHT), octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate ("Irganox 1076" manufactured by BASF), isooctyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate ("Irganox 1135" manufactured by BASF), 3,3',3'',5,5',5" hexa-tert-butyl-a,a',a"-(mesitylene-2,4,6-triyl) tri-p-cresol ("Irganox 1135" manufactured by BASF), 1330”), 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione (“Irganox 3114” manufactured by BASF), 3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane (“ADEKA STAB AO-80” manufactured by ADEKA), 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate (“SUMILIZER GS” manufactured by Sumitomo Chemical), 2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl acrylate (“SUMILIZER GM”), 2,2′-dimethyl-2,2′-(2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diyl)dipropane-1,1′-diyl=bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate] (Sumitomo Chemical “SUMILIZER GA-80”), 1,3,5-tris(3-hydroxy-4-tert-butyl-2,6-dimethylbenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione (Sitech “Cyanox 1790”), etc. The hindered phenol compound is preferably Irganox 1135.
[0078] Examples of the hindered amine compound include bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidyl) sebacate (“Tinuvin 123” manufactured by BASF), tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)butane-1,2,3,4-tetracarboxylate (“ADEKA STAB LA-52” manufactured by ADEKA), tetrakis(2,2,6,6-tetramethyl-4-piperidyl)butane-1,2,3,4-tetracarboxylate (“ADEKA STAB LA-57” manufactured by ADEKA), bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate (“ADEKA STAB LA-72” manufactured by ADEKA), bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate (“ADEKA STAB LA-73” manufactured by ADEKA), and bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate (“ADEKA STAB LA-82” manufactured by ADEKA). LA-77Y”), bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate (ADEKA STAB LA-77G), bis(1-undecanyloxy-2,2,6,6-tetramethylpiperidin-4-yl) carbonate (ADEKA STAB LA-81), 1,2,2,6,6-pentamethyl-4-piperidinyl methacrylate (ADEKA STAB LA-82), 2,2,6,6-tetramethyl-4-piperidinyl methacrylate (ADEKA STAB LA-83), LA-87”), SONGLIGHT 1230 (manufactured by SONGWON), bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate (SONGLIGHT 2920 manufactured by SONGWON), bis(2,2,6,6-tetramethyl-4-piperidyl) sebacate (SONGLIGHT 7700 manufactured by SONGWON), N,N′-bisformyl-N,N′-bis(2,2,6,6-tetramethyl-4-piperidyl)-hexamethylenediamine (Uvinul 4050H manufactured by BASF), bis(2,2,6,6-tetramethyl-4-piperidyl) sebacate (Uvinul 4077H manufactured by BASF), etc. The hindered amine compound is preferably ADEKA STAB LA-52.
[0079] Examples of the phosphorus compound include trioctyl phosphite, trilauryl phosphite, tritridecyl phosphite, triisodecyl phosphite, phenyl diisooctyl phosphite, phenyl diisodecyl phosphite, phenyl ditridecyl phosphite, diphenyl isooctyl phosphite, diphenyl isodecyl phosphite, diphenyl tridecyl phosphite, triphenyl phosphite, tris(nonylphenyl) phosphite, tris(2,4-di-tert-butylphenyl) phosphite, tris(butoxyethyl) phosphite, and tris(biphenyl) phosphite. Ester, tris(3,5-di-tert-butyl-4-hydroxyphenyl)phosphite, 9,10-dihydro-9-phosphaphenanthrene-10-oxide, distearyl pentaerythritol diphosphite, di(nonylphenyl)pentaerythritol diphosphite, phenyl·4,4'-isopropylidene diphenol·pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, phenylbisphenol-A-pentaerythritol diphosphite, etc.
[0080] The amount of the antioxidant to be added is, for example, 0.01 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, or 0.3 parts by weight or more relative to 100 parts by weight of the total of the monomer group and its partial polymer. The upper limit of the amount of the antioxidant to be added is, for example, 5 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, or 0.5 parts by weight or less.
[0081] The adhesive composition may include a crosslinking agent. An example of a crosslinking agent is a multifunctional monomer having two or more polymerizable functional groups in one molecule. The multifunctional monomer may be a (meth)acrylic monomer. An example of a multifunctional monomer is a monomer having two or more C=C bonds in one molecule, and a monomer having one or more C=C bonds and one or more epoxy groups, aziridine groups, The polyfunctional monomer preferably has two or more C═C bonds in one molecule.
[0082] Examples of the crosslinking agent include: polyfunctional acrylates (ester compounds formed by polyols and (meth)acrylic acid, etc.) such as (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,2-ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol diacrylate (NDDA), 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and tetramethylolmethane tri(meth)acrylate; allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, urethane acrylate, butyl di(meth)acrylate, and hexyl di(meth)acrylate. The polyfunctional monomer is preferably a polyfunctional acrylate, and more preferably trimethylolpropane tri(meth)acrylate, hexanediol di(meth)acrylate, or dipentaerythritol hexa(meth)acrylate.
[0083] The amount of the crosslinking agent varies depending on the molecular weight, the number of functional groups, etc., and is, for example, 5 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, and further 0.5 parts by weight or less, relative to 100 parts by weight of the total of the monomer group and its partial polymer. The lower limit of the amount of the crosslinking agent is, for example, 0.01 parts by weight or more, and further 0.05 parts by weight or more.
[0084] The adhesive composition may also contain additives other than those mentioned above. Examples of the additives include chain transfer agents, silane coupling agents, viscosity modifiers, tackifiers, plasticizers, softeners, antioxidants, fillers, colorants, surfactants, antistatic agents, and ultraviolet absorbers.
[0085] The content of the solvent in the adhesive composition is, for example, 5% by weight or less, 4% by weight or less, 3% by weight or less, 2% by weight or less, 1% by weight or less, and further 0.5% by weight or less. The adhesive composition may contain substantially no solvent. Substantially containing no solvent means that a solvent derived from an additive or the like is allowed to be contained at a content of, for example, 0.1% by weight or less, preferably 0.05% by weight or less, and more preferably 0.01% by weight or less.
[0086] The viscosity of the adhesive composition is preferably 5 to 100 poise. An adhesive composition having a viscosity within the above range is particularly suitable for forming a coating layer.
[0087] (Physical properties and characteristics of adhesive sheets)
[0088] The polymerization rate of the monomer group in the pressure-sensitive adhesive sheet 1 is preferably 90% or more. The polymerization rate may be 95% or more, 98% or more, or even 99% or more.
[0089] The gel fraction of the pressure-sensitive adhesive sheet 1 may be, for example, 50% or more, 75% or more, 80% or more, or even 85% or more.
[0090] The creep amount of the pressure-sensitive adhesive sheet 1 is, for example, 180 μm or less, and may be 160 μm or less. The lower limit of the creep amount is, for example, 5 μm or more, and may be 10 μm or more.
[0091] The creep amount of the adhesive sheet 1 can be evaluated as follows (see Figure 2A and Figure 2B ). First, a laminate of the adhesive sheet 1 and the support film 51 to be evaluated is cut into a 10 mm × 50 mm strip to prepare a test piece 52. The support film 51 is configured for the following purpose: to suppress the deformation of the load-applying portion of the adhesive sheet 1 to which the load is applied during the test, thereby measuring the creep amount with higher accuracy. The support film 51 may be, for example, a resin film such as a polyethylene terephthalate (PET) film. The support film 51 may be an optical film or a laminate including an optical film. The thickness of the support film 51 may be a thickness that does not deform due to the above-mentioned load, for example, 20 to 200 μm. Next, as Figure 2A and Figure 2B As shown, a test piece 52 is attached to the surface of a stainless steel test plate 53 using an adhesive sheet 1 for a 10 mm long x 10 mm wide joint surface. Figure 2B yes Figure 2A The test piece 52 is attached to the test plate 53 in such a way that bubbles are not mixed between the test plate 53 and the adhesive sheet 1. In addition, after attachment, the test plate 53 and the adhesive sheet 1 are homogenized by being placed in an autoclave at 50°C and 5 atmospheres (absolute pressure) for 15 minutes. Next, the test plate 53 and the test piece 52 are vertically held in an atmosphere at 25°C in such a way that the test plate 53 is on top. After being placed for at least 5 minutes, a weight of 500 g is fixed at the center of the lower end of the test piece 52 while the test plate 53 is fixed, and a load 54 of 500 gf is applied vertically downward. The creep amount (displacement amount) of the adhesive sheet 1 relative to the test plate 53 at the moment 3600 seconds after the start of the application of the load 54 is measured and used as the amount of weight dropped. The amount of weight dropped can be measured using a laser displacement meter.
[0092] (Method for producing adhesive sheet)
[0093] The adhesive sheet 1 can be produced, for example, by the following method using the above-mentioned adhesive composition. Figure 3As shown, the first laminate 10 including a substrate sheet 11, a coating layer 12 containing an adhesive composition, and a release liner 13 in sequence is irradiated with light 14, and an adhesive sheet 1 with a thickness of 5 to 100 μm is formed from the coating layer 12 (process A). Typically, the irradiation with light 14 is implemented from one side of the substrate sheet 11. The light 14 passes through the substrate sheet 11 and reaches the coating layer 12, so that the coating layer 12 is cured. However, the irradiation with light 14 can also be implemented from one side of the release liner 13, and can also be implemented from both sides of the release liner 13 and the substrate sheet 11. The formed adhesive sheet 1 is sandwiched by the substrate sheet 11 and the release liner 13 to form a part of the second laminate 17 until the release liner 13 is peeled off. After process A, the release liner 13 is peeled off from the adhesive sheet 1 (process B).
[0094] exist Figure 3 In the method, the step A and the step B are repeatedly performed using the release liner 13 peeled off in the step B. Thus, the release liner 13 is reused. The step A using the peeled release liner 13 is performed by forming a first laminate 10 including a base sheet 11, a coating layer 12, and the peeled release liner 13 in this order, and irradiating the formed first laminate 10 with light 14.
[0095] As described above, in the present embodiment, by making the adhesive composition contain antioxidant D, there is a tendency to suppress the increase in the peeling force of the release liner 13 relative to the adhesive sheet 1 when manufacturing the adhesive sheet 1. In detail, in the above-mentioned step A, a chemical bond is generated between the release liner 13 and the adhesive sheet 1 by irradiation with light 14, and a part of it or a functional group formed by the decomposition of the bond sometimes remains on the surface of the release liner 13 after the adhesive sheet 1 is peeled off. As a result, after the implementation of step A, there is a tendency that the peeling force of the release liner 13 relative to the adhesive sheet 1 is increased compared with before the implementation. According to antioxidant D, there is a tendency to suppress the generation of chemical bonds between the release liner 13 and the adhesive sheet 1. In addition, according to antioxidant D, there is a tendency to suppress the surface of the release liner 13 from being contaminated by the material of the adhesive sheet 1 regardless of the manufacturing conditions of the adhesive sheet 1 (light irradiation time, etc.).
[0096] In this embodiment, even when the step A and the step B are repeatedly performed using the release liner 13 peeled off in the step B when manufacturing the adhesive sheet 1, the tendency of the release force of the release liner 13 with respect to the adhesive sheet 1 to increase can be suppressed. Since the release liner 13 can be reused, the amount of waste of the release liner 13 can be reduced, and the adhesive sheet 1 can be manufactured with a low environmental burden.
[0097] <Process A>
[0098] (Release liner)
[0099] An example of the base material of the release liner 13 (hereinafter, "base material") is a resin film. Examples of the resin that can be contained in the base material are polyesters such as polyethylene terephthalate and polyethylene naphthalate, acetate resins, polyether sulfone, polycarbonate, polyamide, polyimide, polyolefin, (meth) acrylic resin, polyvinyl chloride, polyvinylidene chloride, polystyrene, polyvinyl alcohol, polyarylate, and polyphenylene sulfide. The resin is preferably a polyester such as polyethylene terephthalate.
[0100] The release liner 13 may have a transmittance to the light 14 irradiated in the step A, or may have a transmittance to the light 14 of the same degree as that of the base sheet 11 .
[0101] The thickness of the release liner 13 is, for example, 10 to 200 μm, or 25 to 150 μm.
[0102] The release liner 13 may include a layer other than the base material. The release liner 13 may include a release layer. Figure 4 The release liner 13 includes a backing substrate 131 and a release layer 132 formed on one surface of the backing substrate 131 . Figure 4 The release liner 13 may be used in such a manner that the release layer 132 faces the coating layer 12 side.
[0103] Typically, the release layer 132 is a cured layer of a release agent composition containing a release agent. The release agent can use various release agents such as silicone release agents, fluorine release agents, long-chain alkyl release agents, fatty acid amide release agents, and silica powder. The release liner 13 can have a cured layer of a release agent composition containing a silicone release agent as a main component (hereinafter, "silicone release layer"). The silicone release layer is particularly suitable for balancing the adhesion and releasability relative to the adhesive sheet 1. It should be noted that in this specification, the main component refers to the component with the largest content.
[0104] The silicone release agent includes various curable silicone materials such as addition reaction type, condensation reaction type, ultraviolet curing type, electron beam curing type, solvent-free type, etc., preferably addition reaction curing type silicone materials. Addition reaction curing type silicone materials are particularly suitable for forming a release layer that takes into account both adhesion and peelability with respect to the adhesive sheet 1. The curable silicone material can be a silicone modified resin obtained by introducing reactive silicone into an organic resin such as urethane, epoxy, alkyd resin, etc. by graft polymerization.
[0105] Examples of addition reaction curing silicone materials are polyorganosiloxanes having vinyl or alkenyl groups in the molecule. Addition reaction curing silicone materials may not have hydrosilyl groups. Examples of alkenyl groups are 3-butenyl, 4-pentenyl, 5-hexenyl, 6-heptenyl, 7-octenyl, 8-nonenyl, 9-decenyl, 10-undecenyl and 11-dodecenyl. Examples of polyorganosiloxanes are copolymers of polyalkylalkylsiloxanes such as polydimethylsiloxane, polydiethylsiloxane and polymethylethylsiloxane, polyalkylarylsiloxane, and poly(dimethylsiloxane-diethylsiloxane) and other monomers containing Si atoms. Polyorganosiloxane is preferably polydimethylsiloxane.
[0106] A mold release composition containing a silicone-based mold release agent as a main component (hereinafter, "silicone mold release composition") generally contains a crosslinking agent. An example of the crosslinking agent is a polyorganosiloxane having a hydrosilyl group. The crosslinking agent may have two or more hydrosilyl groups in one molecule.
[0107] The silicone release agent composition may also contain a curing catalyst. Examples of the curing catalyst are platinum catalysts. Examples of platinum catalysts are chloroplatinic acid, olefin complexes of platinum, and olefin complexes of chloroplatinic acid. The amount of the platinum catalyst used is, for example, 10 to 1000 ppm (weight basis, converted to platinum) relative to the total solid content of the composition.
[0108] The silicone release agent composition may also contain additives. Examples of additives are release control agents and adhesion improvers. Examples of release control agents are unreactive silicone resins, and more specifically, organosiloxanes such as octamethylcyclotetrasiloxane and MQ resins. The total amount of release control agents and adhesion improvers is, for example, 1 to 30% by weight relative to the total solid content of the composition. Other examples of additives are fillers, antistatic agents, antioxidants, ultraviolet absorbers, plasticizers, and colorants. The total amount of other additives is, for example, 10% by weight or less relative to the total solid content of the composition.
[0109] The silicone release agent composition may also contain an organic solvent. Examples of organic solvents are hydrocarbon solvents such as cyclohexane, n-hexane, and n-heptane; aromatic solvents such as toluene and xylene; ester solvents such as ethyl acetate and methyl acetate; ketone solvents such as acetone and methyl ethyl ketone; and alcohol solvents such as methanol, ethanol, and butanol. Two or more organic solvents may also be contained. The amount of organic solvent used is preferably 80 to 99.9% by weight of the silicone release agent composition.
[0110] The release layer 132 can be formed, for example, by heating and drying a coating film containing a release agent composition formed on the lining substrate 131. The release agent composition can be applied by various coating methods such as roller coating, roller lick coating, gravure coating, reverse coating, roller brush, spray coating, dip roller coating, rod coating, blade coating, air knife coating, shower coating, die lip coating, and die coating. Heating and drying can be performed by hot air drying, for example. The heating temperature and time vary depending on the heat resistance of the lining substrate, and are generally 80 to 150° C. and about 10 seconds to 10 minutes. As required, irradiation with active energy rays such as ultraviolet rays can also be used in combination.
[0111] The thickness of the release layer 132 is, for example, 10 to 300 nm. The upper limit of the thickness may be 200 nm or less, 150 nm or less, 120 nm or less, 110 nm or less, 100 nm or less, less than 100 nm, 90 nm or less, 80 nm or less, 70 nm or less, less than 70 nm, and further may be 65 nm or less. The lower limit of the thickness may be 15 nm or more, 20 nm or more, 25 nm or more, 30 nm or more, 35 nm or more, 40 nm or more, 45 nm or more, and further may be 50 nm or more. The thickness of the release layer 132 may be 110 nm or less. In other words, the release liner 13 may have a release layer 132 on the surface of the coating layer 12, and the thickness of the release layer 132 may be 110 nm or less.
[0112] The release liner 13 may be in the form of a single sheet or in the form of a long strip.
[0113] (Base sheet)
[0114] An example of the base sheet 11 is a resin film. Examples of the resin contained in the base sheet 11 are the same as examples of the resin that may be contained in the backing base.
[0115] The base sheet 11 preferably has excellent transmittance to the light 14 irradiated in the step A.
[0116] The thickness of the base sheet 11 is, for example, 10 to 200 μm, or 25 to 150 μm.
[0117] The substrate sheet 11 may be provided with a release layer on the surface of the coating layer 12 side. The examples of the release layer and its preparation method that the substrate sheet 11 may have are the same as the examples of the release layer and its preparation method that the release liner 13 may have. The release layer may be provided on both the release liner 13 and the substrate sheet 11. In this case, the release layers of the two may be formed by a release agent composition containing the same release agent as a main component. In addition, the thickness of the release layers of the two may also be different, for example, the release layer provided by the substrate sheet 11 may be thicker.
[0118] The base sheet 11 can generally be selected to have a greater release force with the pressure-sensitive adhesive sheet 1 than the release liner 13 .
[0119] The base sheet 11 may be in the form of a single sheet or in the form of a long strip.
[0120] (First Laminated Body and Formation thereof)
[0121] The first laminate 10 may include another layer in addition to the base sheet 11, the coating layer 12, and the release liner 13. The other layer may be disposed on the side of the base sheet 11 and / or the release liner 13 opposite to the coating layer 12 side. The coating layer 12 is preferably in contact with the base sheet 11 and the release liner 13.
[0122] The first laminate 10 can be formed, for example, by forming a coating layer 12 on a substrate sheet 11 (or a release liner 13), and disposing a release liner 13 (or a substrate sheet 11) on the formed coating layer 12. Alternatively, the first laminate 10 can be formed by coating the adhesive composition so that it flows into a space between the substrate sheet 11 and the release liner 13, which are kept at a predetermined interval so that their main surfaces face each other. The release liner 13 after release can be used so that the surface on the coating layer 12 side, for example, the surface on the release layer 132 side, in the step A immediately before release becomes the coating layer 12 side again.
[0123] The coating layer 12 can be formed by various coating methods such as roll coating, lick roll coating, gravure coating, reverse coating, roller brushing, spray coating, dip roll coating, rod coating, blade coating, air knife coating, shower coating, die lip coating, and die coating.
[0124] The thickness of the coating layer 12 can be adjusted according to the target thickness of the pressure-sensitive adhesive sheet 1 , and may be, for example, 5 to 100 μm, 5 to 50 μm, 5 to 25 μm, or even 5 to 20 μm.
[0125] The first laminate 10 may include a long strip substrate sheet 11, a long strip coating layer 12 and a long strip release liner 13. In other words, it may be in a long strip shape. The long strip first laminate 10 may be obtained by, for example, conveying the substrate sheet 11 and the release liner 13 continuously unwound from a roll while forming the coating layer 12 therebetween.
[0126] (Radiation of light)
[0127] The light 14 irradiated to the first stack 10 is, for example, visible light or ultraviolet light having a wavelength shorter than 450 nm. The light 14 may include light of a wavelength in the same region as the absorption wavelength of the photopolymerization initiator contained in the adhesive composition. The light 14 obtained by cutting off short-wavelength light with a wavelength of less than 300 nm through an optical filter or the like may be irradiated, and cutting off the short-wavelength light is suitable for suppressing the degradation of the substrate sheet 11 caused by the light 14. The light source of the light 14 is, for example, an irradiation device having an ultraviolet irradiation lamp. Examples of ultraviolet irradiation lamps are ultraviolet LEDs, low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, xenon lamps, microwave-excited mercury lamps, black light lamps, chemical lamps, sterilization lamps, low-pressure discharge mercury lamps, and excimer lasers. Two or more ultraviolet irradiation lamps may also be combined.
[0128] The irradiation of the light 14 may be continuous or intermittent.
[0129] The illuminance of the light 14 is, for example, 1 to 20 mW / cm 2 The irradiation time of the light 14 is, for example, 5 minutes to 5 hours. The cumulative light intensity of the light 14 on the first stacked body 10 is, for example, 100 to 5000 mJ / cm 2 .
[0130] <Process B>
[0131] In step B, the release liner 13 is peeled off from the cured second laminate 17. The second laminate 17 sequentially comprises the base sheet 11, the pressure-sensitive adhesive sheet 1, and the release liner 13. By the above peeling, the release liner 13 and the third laminate 15 comprising the base sheet 11 and the pressure-sensitive adhesive sheet 1 are obtained.
[0132] The peeling force between the release liner 13 and the pressure-sensitive adhesive sheet 1 is smaller than the peeling force between the substrate sheet 11 and the pressure-sensitive adhesive sheet 1. The peeling force between the substrate sheet 11 and the pressure-sensitive adhesive sheet 1 is, for example, 0.1 to 10 N / 50 mm, 1 to 8 N / 50 mm, 2 to 7 N / 50 mm, or 3 to 5 N / 50 mm.
[0133] The number of times the release liner 13 is peeled off and reused for the production of the pressure-sensitive adhesive sheet 1 is not particularly limited, and may be, for example, 3 times or more, 5 times or more, or 7 times or more.
[0134] The peeled release liner 13 can be recycled after being wound into a roll.
[0135] <Peel force between pressure-sensitive adhesive sheet and release liner>
[0136] In this embodiment, the peeling force PS between the release liner 13 and the PSA sheet 1 after being peeled off from the PSA sheet 1 n times is counted starting from the unused state. n(n is an integer greater than or equal to 0 corresponding to the number of peelings; when n=0, the peeling force PS0 in an unused state) is preferably 1.0 N / 50 mm or less.
[0137] As an example, the peeling force PS0 between the release liner 13 and the adhesive sheet 1 in an unused state is not particularly limited, and is, for example, 1.0 N / 50 mm or less, 0.5 N / 50 mm or less, 0.2 N / 50 mm or less, 0.15 N / 50 mm or less, 0.12 N / 50 mm or less, 0.1 N / 50 mm or less, 0.08 N / 50 mm or less, and further 0.05 N / 50 mm or less. The peeling force PS0 may be 0.01 N / 50 mm or more, 0.02 N / 50 mm or more, and further 0.03 N / 50 mm or more.
[0138] The peeling force PS1 between the release liner 13 and the adhesive sheet 1 after being peeled off once from the adhesive sheet 1 is preferably 1.0 N / 50 mm or less, and can be 0.9 N / 50 mm or less, 0.8 N / 50 mm or less, 0.7 N / 50 mm or less, 0.6 N / 50 mm or less, 0.5 N / 50 mm or less, 0.4 N / 50 mm or less, 0.3 N / 50 mm or less, 0.2 N / 50 mm or less, and further can be 0.15 N / 50 mm or less. The lower limit of the peeling force PS1 is, for example, 0.01 N / 50 mm or more, 0.03 N / 50 mm or more, 0.05 N / 50 mm or more, 0.08 N / 50 mm or more, and further can be 0.1 N / 50 mm or more.
[0139] The ratio PS1 / PS0 of the peel force PS1 to the peel force PS0 may be 10 or less, 8 or less, 6 or less, or even 5 or less. The lower limit of the ratio PS1 / PS0 is, for example, 1.1 or more, or 2.0 or more.
[0140] Peel force PS nThe evaluation can be performed by using the above-mentioned release liner 13 to implement step A and step B n times, and using the second laminate 17 formed by further implementing the (n+1)th step A, and by the following method. In detail, the second laminate 17 formed by implementing step A can be cut out to a width of 50 mm to make a test piece, and a 180° peeling test can be performed to peel only the release liner 13 from the prepared test piece. The peeling test is performed after about 0.5 to 1 hour has passed after the adhesive sheet 1 is formed. From the formation of the adhesive sheet 1 to the implementation of the peeling test, the second laminate 17 and the test piece are placed in an atmosphere of 23°C±5°C. The peeling speed of the peeling test is set to 300 mm / min, and the test temperature is set to 23°C±5°C. In the case where the width of the second laminate 17 does not meet 50 mm, the measured value at the original width can be converted into a value when the width is 50 mm. When the formation direction of the coating layer 12 can be identified, TD, which is perpendicular to the MD in the plane, can be determined as the width direction of the test piece. When the substrate sheet 11 and the release liner 13 are long, their width direction can be used as the width direction of the test piece.
[0141] Next, refer to Figure 5 Another example of the method for manufacturing the adhesive sheet 1 is described. In this example, a coating layer 12 of an adhesive composition is formed by a coating device 32 on one side of a long substrate sheet 11 continuously unrolled from a roll 31. Next, a long release liner 13 continuously unrolled from a roll 33 is arranged on the coating layer 12 to form a long first laminate 10. Next, the first laminate 10 is irradiated with light 14 from a lighting device 34 to form a long adhesive sheet 1. Next, the release liner 13 is peeled off from the second laminate 17 containing the adhesive sheet 1 and wound on a roll 35. The above steps are implemented while conveying the substrate sheet 11 and the release liner 13. The release liner 13 after winding is reused. Figure 5 The method is particularly suitable for mass production of the adhesive sheet 1.
[0142] Reference Figure 6 Another example of the method for producing the pressure-sensitive adhesive sheet 1 is described. This example is similar to the method described above except that the release liner 13 peeled from the second laminate 17 is not wound into a roll 35 but is reused in the production of the pressure-sensitive adhesive sheet 1. Figure 5 Same as the example. Figure 6 The method is particularly suitable for mass production of the adhesive sheet 1.
[0143] [Embodiments of Optical Film with Pressure-Sensitive Adhesive Sheet]
[0144] An example of the optical film with a pressure-sensitive adhesive sheet according to the present embodiment is shown in Figure 7 . Figure 7The optical film 20A with an adhesive sheet includes an adhesive sheet 1 and an optical film 2. The adhesive sheet 1 may be directly or indirectly in contact with the optical film 2. The optical film 20A with an adhesive sheet may have a structure in which a base sheet used when making the adhesive sheet 1 is laminated on the adhesive sheet 1.
[0145] The optical film 2 is, for example, a film including at least one selected from a polarizing film and a phase difference film. The optical film 2 may be a laminated film including a polarizing film and / or a phase difference film. The optical film 2 may include a film made of glass. However, the optical film 2 is not limited to the above examples.
[0146] The polarizing film includes a polarizer. Typically, the polarizing film includes a polarizer and a protective film (transparent protective film). The protective film is, for example, arranged in contact with the main surface (surface with the widest area) of the polarizer. The polarizer can be arranged between two protective films. The protective film can be arranged on at least one side of the polarizer.
[0147] The polarizer is not particularly limited, and examples thereof include: a polarizer obtained by adsorbing a dichroic substance such as iodine and a dichroic dye on a hydrophilic polymer film such as a polyvinyl alcohol film, a partially formalized polyvinyl alcohol film, and a partially saponified film of an ethylene-vinyl acetate copolymer, and then uniaxially stretching the film; a polyene oriented film such as a dehydrated product of polyvinyl alcohol and a dehydrochlorinated product of polyvinyl chloride, etc. Typically, the polarizer is formed of a polyvinyl alcohol film (polyvinyl alcohol films include partially saponified films of ethylene-vinyl acetate copolymers) and a dichroic substance such as iodine.
[0148] The thickness of the polarizer is not particularly limited, for example, it is 80 μm or less, it can be 50 μm or less, 30 μm or less, 25 μm or less, and further, it can be 20 μm or less. The lower limit of the thickness of the polarizer is not particularly limited, for example, it is 1 μm or more, it can be 5 μm or more, 10 μm or more, and further, it can be 15 μm or more. The dimensional change of the thin polarizer (for example, the thickness is 20 μm or less) is suppressed, which can contribute to the durability of the optical laminate, especially the durability at high temperature.
[0149] As the material of the protective film, for example, a thermoplastic resin having excellent transparency, mechanical strength, thermal stability, moisture barrier, isotropy, etc. can be used. Specific examples of such thermoplastic resins include cellulose resins such as cellulose triacetate, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins (norbornene resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. The material of the protective film can be a thermosetting resin or ultraviolet curing resin such as (meth)acrylic acid, urethane, acrylic urethane, epoxy, silicone, etc. In the case where the polarizing film has two protective films, the materials of the two protective films can be the same or different from each other. For example, a protective film formed of a thermoplastic resin can be bonded to one main surface of the polarizer via an adhesive, and a protective film formed of a thermosetting resin or an ultraviolet curing resin can be bonded to the other main surface of the polarizer. The protective film can contain one or more arbitrary additives. Examples of the additive include ultraviolet absorbers, antioxidants, lubricants, plasticizers, release agents, anti-coloring agents, flame retardants, nucleating agents, antistatic agents, pigments, and colorants.
[0150] The thickness of the protective film can be appropriately determined, and is generally about 10 to 200 μm from the perspectives of strength, workability such as handling properties, and thin film properties.
[0151] The polarizer and the protective film are usually bonded together via a water-based adhesive or the like. Examples of the water-based adhesive include isocyanate adhesives, polyvinyl alcohol adhesives, gelatin adhesives, vinyl latex, water-based polyurethane, and water-based polyester. Other adhesives other than the above-mentioned adhesives include ultraviolet curing adhesives and electron beam curing adhesives. Electron beam curing polarizer adhesives show suitable adhesion to various protective films. The adhesive may also contain a metal compound filler.
[0152] In the polarizing film, a retardation film or the like may be formed on the polarizer instead of the protective film. Another protective film or a retardation film or the like may be provided on the protective film.
[0153] The protective film may be provided with a hard coating layer on the surface opposite to the surface bonded to the polarizer, and may be subjected to treatment for the purpose of anti-reflection, anti-blocking, diffusion, anti-glare, etc.
[0154] The polarizing film may be a circular polarizing film.
[0155] As the retardation film, a film obtained by stretching a polymer film or a film obtained by orienting and fixing a liquid crystal material can be used. The retardation film has birefringence in the plane and / or in the thickness direction, for example.
[0156] The phase difference film includes a phase difference film for antireflection (refer to Japanese Patent Application Publication No. 2012-133303
[0221] ,
[0222] , and
[0228] ), a phase difference film for viewing angle compensation (refer to Japanese Patent Application Publication No. 2012-133303
[0225] and
[0226] ), and a tilted orientation phase difference film for viewing angle compensation (refer to Japanese Patent Application Publication No. 2012-133303
[0227] ).
[0157] The specific structure of the retardation film, such as the retardation value, the arrangement angle, the three-dimensional birefringence, whether it is a single layer or a multilayer, etc., is not particularly limited, and a known retardation film can be used.
[0158] The thickness of the retardation film is preferably 20 μm or less, more preferably 10 μm or less, further preferably 1 to 9 μm, particularly preferably 3 to 8 μm.
[0159] The phase difference film may include, for example, a quarter wave plate and / or a half wave plate in which a liquid crystal material is oriented and fixed.
[0160] The optical film 20A with an adhesive sheet can be formed, for example, by placing an optical film 2 on the exposed surface of an adhesive sheet 1 formed by peeling off the release liner 13 from a second laminate 17 sequentially including a substrate sheet 11, an adhesive sheet 1, and a release liner 13, and laminating the adhesive sheet 1 and the optical film 2. The second laminate 17 can be formed by the above-mentioned step A. The peeling of the release liner 13 can be carried out as the above-mentioned step B.
[0161] Another example of the optical film with a pressure-sensitive adhesive sheet according to the present embodiment is shown in Figure 8 . Figure 8 The optical film 20B with an adhesive sheet has a laminated structure in which an adhesive sheet 1A, an optical film 2A, an adhesive sheet 1B, and an optical film 2B are laminated in this order. The optical film 20B with an adhesive sheet may have a structure in which a base sheet used when manufacturing the adhesive sheet 1A is laminated on the adhesive sheet 1A.
[0162] In the optical film 20B with a pressure-sensitive adhesive sheet, typically, the optical film 2A is a phase difference film, and the optical film 2B is a polarizing film. The pressure-sensitive adhesive sheet 1B functions as an interlayer pressure-sensitive adhesive between the optical films 2A and 2B. A known pressure-sensitive adhesive can be used for the pressure-sensitive adhesive sheet 1B.
[0163] The optical film with an adhesive sheet of the present embodiment can be distributed and stored in the form of a roll formed by winding a tape-shaped optical film with an adhesive sheet or in the form of a single sheet of the optical film with an adhesive sheet.
[0164] Typically, the optical film with an adhesive sheet of the present embodiment can be used in an image display device. The image display device can be formed by, for example, bonding the optical film 20A or 20B with an adhesive sheet to an image display panel. The bonding is performed, for example, through the adhesive sheet 1. The image display device can be an organic EL display or a liquid crystal display. However, the image display device is not limited to the above examples. The image display device can also be a field luminescence (EL) display, a plasma display (PD), a field emission display (FED: Field Emission Display), etc. The image display device can be used for household appliances, in-vehicle uses, public information displays (PID) uses, etc.
[0165] Example
[0166] Hereinafter, the present invention will be described in more detail by way of examples. However, the present invention is not limited to the examples shown below.
[0167] (Example 1)
[0168] [Preparation of Release Liner A]
[0169] 30 parts by weight of an addition reaction curable silicone (LTC761 containing hexenyl group-containing polyorganosiloxane, 30% by weight toluene solution, manufactured by Dow Corning Toray), 0.9 parts by weight of a release control agent (BY24-850 containing unreacted silicone resin, manufactured by Dow Corning Toray), 2 parts by weight of a curing catalyst (SRX212 containing a platinum catalyst, manufactured by Dow Corning Toray), and a toluene / hexane mixed solvent (volume ratio 1:1) as a diluent were mixed to obtain a silicone-based release agent composition A. The concentration of the silicone solid content in the release agent composition A was 1.0% by weight. Next, the release agent composition A was applied to one side of a liner substrate (Lumirror XD500P as a polyester film, thickness 75 μm) using a wire bar, and heated at 130° C. for 1 minute to prepare a release liner A having a release layer (thickness 60 nm) on one side.
[0170] [Preparation of Adhesive Composition A]
[0171] 95.1 parts by weight of n-butyl acrylate (BA), 4.8 parts by weight of acrylic acid (AA), 0.1 parts by weight of 4-hydroxybutyl acrylate (HBA), 0.05 parts by weight of 2,2-dimethoxy-1,2-diphenylethane-1-one (Omnirad651, manufactured by IGM Resins BV) as a photopolymerization initiator, and 0.05 parts by weight of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (Omnirad819, manufactured by IGM Resins BV) were placed in a four-necked flask and irradiated with ultraviolet rays in a nitrogen atmosphere to obtain a partially photopolymerized monomer syrup. The ultraviolet irradiation was performed until the viscosity of the liquid in the flask (measurement conditions: BH viscometer No. 5 rotor, 10 rpm, measurement temperature 30°C) reached about 20 Pa·s. Next, 0.09 parts by weight of 1,9-nonanediol diacrylate (NDDA) as a crosslinking agent and 0.3 parts by weight of isooctyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate ("Irganox 1135" manufactured by BASF) as an antioxidant were added to 100 parts by weight of the monomer syrup and uniformly mixed to obtain an adhesive composition A.
[0172] [Evaluation of Peel Force PS0]
[0173] Adhesive composition A was applied to one side of a substrate sheet (Lumirror XD500P, 75 μm thick, which is a polyester film without a release layer) using an applicator to form a coating layer (20 μm thick). Next, a release liner A was placed on the formed coating layer to obtain the first laminate. The release liner A was placed so that the release layer and the coating layer were in contact. Next, the coating layer was exposed to light at an illumination of 2.42 mW / cm 2 The first laminate was irradiated with ultraviolet light (black light source) from one side of the substrate sheet for 10 minutes to photocure the coating layer, thereby forming a second laminate consisting of a substrate sheet, an adhesive sheet (thickness 20 μm) and a release liner A.
[0174] A test piece of 220 mm in length and 50 mm in width was cut out from the formed second laminate (the length direction is the coating direction of the adhesive composition). A 180° peeling test was performed on the test piece using a tensile tester, in which only the release liner A was peeled off along the length direction, and the peeling force PS0 was evaluated. The conditions of the peeling test were as described above.
[0175] [Evaluation of Peel Force PS1]
[0176] The second laminate was prepared by the same method as the evaluation of the peeling force PS0, and the release liner A was peeled off from the adhesive sheet. Next, the first laminate was formed, the second laminate was formed by ultraviolet irradiation, the test piece was cut out, and the peeling force was evaluated by the same method as above using the peeled release liner A. Thus, the peeling force PS1 was evaluated.
[0177] (Example 2)
[0178] [Preparation of Release Liner B]
[0179] A release liner B having a release layer (thickness 120 nm) on one surface was prepared by the same method as the method for preparing the release liner A except that the thickness of the release agent composition A applied to the liner was changed.
[0180] [Evaluation of Peel Force PS0]
[0181] A PSA sheet was produced in the same manner as in Example 1 except that the release liner B was used. Furthermore, in the same manner as in Example 1, the release force PS0 was evaluated using the second laminate including the PSA sheet.
[0182] [Evaluation of Peel Force PS1]
[0183] The second laminate was prepared by the same method as the evaluation of the peeling force PS0, and the release liner B was peeled off from the adhesive sheet. Next, using the release liner B peeled off from the adhesive sheet, an adhesive sheet was prepared by the same method as in Example 1. Furthermore, the peeling force PS1 was evaluated by the same method as in Example 1 using the second laminate including the adhesive sheet.
[0184] (Examples 3 to 5)
[0185] PSA sheets were prepared for Examples 3 to 5 in the same manner as in Example 2 except that the ultraviolet irradiation conditions during the preparation of the PSA sheet were changed as shown in Table 1, and the peeling forces PS0 and PS1 were evaluated.
[0186] (Examples 6-7)
[0187] PSA sheets were prepared for Examples 6 and 7 in the same manner as in Example 2 except that the compounds listed in Table 1 were used as the antioxidant contained in the PSA composition A, and the peel forces PS0 and PS1 were evaluated.
[0188] (Comparative Example 1)
[0189] Adhesive composition B was prepared in the same manner as Adhesive composition A except that no antioxidant was used. A PSA sheet was prepared for Comparative Example 1 in the same manner as Example 2 except that PSA composition B was used, and the peel forces PS0 and PS1 were evaluated.
[0190] [Table 1]
[0191]
[0192] The abbreviations in Table 1 are as follows.
[0193] Irg1135: 2-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate ("Irganox 1135" manufactured by BASF, molecular weight 390)
[0194] LA-52: Tetrakis(1,2,2,6,6-pentamethyl-4-piperidinyl)butane-1,2,3,4-tetracarboxylate ("ADEKA STAB LA-52" manufactured by ADEKA Corporation, molecular weight 847)
[0195] 2112: Tris(2,4-di-tert-butylphenyl)phosphite ("ADEKA STAB2112" manufactured by ADEKA Corporation, molecular weight 647)
[0196] As shown in Table 1, in the example in which the adhesive sheet having a thickness of 5 to 100 μm was prepared using the adhesive composition containing the above-mentioned antioxidant D, the peeling force PS1 was a smaller value than that of the comparative example. As such, in the example, there is a tendency that the peeling force of the release liner relative to the adhesive sheet can be suppressed from increasing even if the release liner is reused when the adhesive sheet is manufactured. Thus, the amount of waste of the release liner can be reduced, and the adhesive sheet can be manufactured with a low environmental burden.
[0197] Industrial Applicability
[0198] The pressure-sensitive adhesive sheet of the present invention can be used for, for example, an optical layered body or an image display device.
Claims
1. An adhesive sheet, which is formed from a photocurable adhesive composition, wherein the photocurable adhesive composition comprises a monomer group containing a (meth)acrylic monomer and / or a partial polymer of the monomer group, and a photopolymerization initiator, The thickness of the adhesive sheet is 5 to 100 μm. The adhesive composition further comprises an antioxidant, The antioxidant comprises at least one selected from hindered phenol compounds, hindered amine compounds and phosphorus compounds, and has a molecular weight of less than 1000.
2. The adhesive sheet according to claim 1, wherein The antioxidant comprises a hindered phenol compound.
3. The adhesive sheet according to claim 1, wherein The molecular weight of the antioxidant is 500 or less.
4. The adhesive sheet according to claim 1, wherein In 100 parts by weight of the monomer group, the blending amount of the hydroxyl group-containing monomer is less than 5 parts by weight.
5. The adhesive sheet according to claim 1, wherein The monomer group includes a carboxyl group-containing monomer.
6. The adhesive sheet according to claim 1, wherein The content of the solvent in the adhesive composition is 5% by weight or less.
7. An optical film with an adhesive sheet, comprising: The adhesive sheet according to any one of claims 1 to 6, and Optical film.
8. The optical film with a pressure-sensitive adhesive sheet according to claim 7, wherein The optical film is a film including at least one selected from a polarizing film and a phase difference film.
9. A method for producing a pressure-sensitive adhesive sheet, which is the method for producing a pressure-sensitive adhesive sheet according to any one of claims 1 to 6, The manufacturing method comprises: A step A of irradiating a laminate including a substrate sheet, a coating layer containing the adhesive composition, and a release liner in this order with light to form the adhesive sheet having a thickness of 5 to 100 μm from the coating layer; and step B of peeling the release liner from the pressure-sensitive adhesive sheet, The step A and the step B are repeatedly performed using the release liner released in the step B, and the release liner is reused.
10. A method for manufacturing an optical film with an adhesive sheet, the method comprising: The pressure-sensitive adhesive sheet formed by the production method according to claim 9 is laminated on an optical film to form an optical film with a pressure-sensitive adhesive sheet.
Citation Information
Patent Citations
Optical display device having polarizing film
JP2012133303A